How Do Arabidopsis Seedlings Sense and React to Increasing Ambient Temperatures? - Attila Fehér; Rasik Shiekh Bin Hamid; Zoltán Magyar (Plants)
Plants respond to higher ambient temperatures by modifying their growth rate and habitus. This review aims to summarize the accumulated knowledge obtained with Arabidopsis seedlings grown at normal and elevated ambient temperatures. Thermomorphogenesis in the shoot and the root is overviewed separately, since the experiments indicate differences in key aspects of thermomorphogenesis in the two organs. This includes the variances in thermosensors and key transcription factors, as well as the predominance of cell elongation or cell division, respectively, even though auxin plays a key role in regulating this process in both organs. Recent findings also highlight the role of the root and shoot meristems in thermomorphogenesis and suggest that the cell cycle inhibitor RETINOBLASTOMA-RELATED protein may balance cell division and elongation at increased temperatures.